Development of Smart Solar Charge Controller on Wiznet W5500 IoT Platform - M.V.N., Srujan Manohar; O.A., Varun; P., Lavanya; Y., Sathwik; M., Madhu (Journal of ISMAC, 2024)
The research represents a significant advance in solar energy technology, taking inspiration from nature's own efficiency mechanisms, particularly the heliotropic behavior of sunflowers. This research proposes the development and implementation of a solar energy system that dynamically adjusts the position of solar panels to track the movement of the sun throughout the day, maximizing energy capture and efficiency. The system uses a biomimetic approach, replicating the natural response of sunflowers to optimize exposure to sunlight. The main components of the system include LDR sensors for real-time sun position tracking, actuators for panel orientation adjustments, and a central control unit to manage system operations. This proposed study aims to address the limitations of traditional fixed solar panel systems, which are unable to adapt to changing sunlight angles throughout the day. The proposed system is also includes a MPPT based solar charge controller, with its response accessible through web servers and laptops/cell phones. The W5500 web server module integrated into the system serves as an IoT platform. Since web servers are platform-independent, they can be supported in cell phones/laptops allowing users to request relay evaluations and monitor solar charge controllers through the W5500 modules. The system can display battery charging status under various weather conditions and can be further enhanced to track other devices. The solar charge controller features multiple modules that enable IoT functionality, such as WIZNET (W5500), Arduino Nano (Atmega 328p), ESP32, solar panels, servo which are low cost and energy efficient.
Keywords: MPPT Module CN3791; Solar Panels (5V); Servo Motors (90g); Arduino Nano; WIZNET W5500; ESP 32